Teammate influences, psychological well‐being, and athletes' eating and exercise psychopathology: A moderated mediation analysis. Issue 4 (10th January 2020) - Scott, Charlotte L.; Plateau, Carolyn R.; Haycraft, Emma
Abstract: Objective: Positive and negative influences from teammates (e.g., supportive teammate friendships, modelling of teammates' disordered eating) have been associated with athletes' eating/exercise psychopathology. However, research is yet to explore how an athlete's psychological well‐being and gender may impact upon these relationships. This study aimed to explore whether psychological well‐being mediates the relationship between teammate influences and eating/exercise psychopathology, and to determine whether gender moderates the significant mediation effects identified. Method: Athletes ( N = 195, mean age 18.35 years, n = 110 female, n = 81 lean sport athletes) completed a survey three times over an 8‐month period exploring teammate influences, psychological well‐being (self‐esteem, anxiety, depression) and eating/exercise psychopathology. Mediation and moderated‐mediation analyses were conducted. Results: Higher levels of anxiety significantly mediated the positive relationships between bulimia modelling and teammate pressure with eating and exercise psychopathology. Higher levels of depression significantly mediated the positive relationship between teammate pressure and body dissatisfaction, and the negative relationship between supportive friendships and body dissatisfaction. Higher levels of self‐esteem mediated both inverse relationships between supportive friendships and a lower drive for thinness (fully) and body dissatisfaction (partially). Gender did not significantly moderate any mediation relationships. Discussion: Male and female athletes with poor psychological well‐being (i.e., high levels of anxiety or depression) are more susceptible to negative teammate influences, while athletes with good psychological well‐being (i.e., high self‐esteem) reap the protective benefits of supportive teammate friendships. Understanding the circumstances under which teammates are influential is vital for the development of targeted intervention and prevention strategies to reduce athlete eating and exercise psychopathology.